Dinâmica espaço – temporal do bacterioplâncton em um sistema de várzea Amazônico - Reis, Mariana Câmara dos (2017)
Amazonian floodplains are complex networks that play relevant roles in global biogeochemical cycles, and the bacterioplankton degradation of organic matter is key in regional carbon budget in these systems. The Amazon undergoes seasonal variations in water level, which produces changes in landscape and in sources of organic inputs into floodplain systems. Although these changes should affect bacterioplankton, no studies have addressed the question of which factors drive spatial and temporal patterns of bacterioplankton in these systems. We used high-throughput (Illumina MiSeq) sequencing of the V3-V4 region of the 16SrRNA gene to investigate the spatiotemporal patterns of bacterioplankton community at different diversity layers and size fractions, and their correlation with environmental variables in an Amazon floodplain lake. Overall, four phyla dominated the community throughout the study: Actinobacteria, Cyanobacteria, Proteobacteria and Planctomycetes, but their abundance were different between size fractions, hydrologic periods and influence area. The rare biosphere had an important contribution for the composition patterns of all community and showed be more influenced by the spatial complexity. We found that the floodpulse was the mainly drive force of community composition patterns for the free-living fraction, and the distance from the Amazon river was the main driver for the particle-attached fraction. We also found differences between the combination of local and regional factors across space and time shaping the community. This is the first detailed characterization of the bacterioplankton community composition in an Amazon floodplain lake and we demonstrated that the spatial and temporal complexity of this system were reflected in bacterioplankton community composition.